Language and Culture in Health Literacy for People Living with HIV: Perspectives of Health Care Providers and Professional Care Team Members - Keitshokile Dintle Mogobe; Sheila Shaibu; Ellah Matshediso; Motshedisi Sabone; Esther Ntsayagae; Patrice K. Nicholas; Carmen J. Portillo; Inge B. Corless; Carol Dawson Rose; Mallory O. Johnson; Allison Webel; Yvette Cuca; et al. (AIDS Research and Treatment, 2016)
Low health literacy has been linked to inadequate engagement in care and may serve as a contributor to poor health outcomes among people living with HIV and AIDS. The purpose of this paper was to examine the perspectives of health care providers and professional care team members regarding health literacy in HIV disease. A secondary data analysis was conducted from a qualitative study aimed at understanding factors that help an HIV positive person to manage their HIV disease. Data were collected from sites in Botswana, the US, and Puerto Rico. In the parent study, data were collected through focus group discussions with 135 people living with HIV, 32 HIV health care providers (HCPs), and 39 HIV professional care team members (PCTMs). SPSS was used to analyze quantitative data while ATLAS.ti was used to analyze qualitative data. The findings from analyses of the perspectives of HCPs/PCTMs suggested that linguistic and cultural factors were important themes in the exchange of HIV information between health care providers and PLHIV. These themes included ineffective communication, health seeking behavior, cultural facilitators, and complementary and alternative/traditional healing methods. Thus, this study suggests that language and culture have a major role in health literacy for PLHIV.